PERANAN KAUNSELING PERSPEKTIF ISLAM DALAM MEMBANTU ATASI RASA FOBIA MANGSA COVID-19 - Mohamad Hassan, Nurhalimah; Yahya, Siti Aishah (Jurnal ’Ulwan, 2023)
This concept paper discusses the role of Islamic counseling in helping overcome phobias among covid-19 victims. This paper also discusses the factors that cause phobias in individuals, especially among victims of covid19. According to a Metro newspaper report dated May 21, 2021, as many as 85.5 percent of the 150,000 calls received by any government agency from March 25, 2020 until May 20, 2021 involved mental health issues that require emotional support and counseling services such as acute stress , anxiety, depression, abuse and suicidal behavior. This clearly proves that the covid-19 pandemic has an impact on human life not only from the economic aspect, physical health but also affects the mental health of the community especially in Malaysia. In addition, this paper also discusses the approach of Islamic counseling in helping victims of covid-19 overcome their phobias in order to continue their daily lives despite the different norms of life as before the pandemic. Therefore, with the result of this concept paper, it can give exposure to counselors in applying Islamic counseling to help victims of covid-19 in overcoming their phobias. Finally, the production of this concept paper can help the community in maintaining mental health post-pandemic in addition to being able to strengthen the role of counselors in the application of Islamic counseling in helping victims of covid19 to overcome the problem of phobias in themselves.